MẶT SAN BẰNG TRÊN CAO NGUYÊN KON PLÔNG, NHỮNG NHẬN THỨC BAN ĐẦU - An, Lê Đức; Thịnh, Võ; Tuấn, Ngô Anh (Vietnam Journal of Earth Sciences, 2005)
Plateau Kon Plong belongs to the central part of Truong Son Nam ridge being the area of drainage divide of 5 river basins : Oak Bla, Tra Khuc, Ve, Con (Ha Giao) and Ba.Four steps of relief are defined in this region ; they are planation surfaces of pediplain and pediment types. Due to new finding of Neogene deposits on the plateau surface we can define the age for these planation surfaces, as following: surface of plateau (1,200 m) - Middle Miocene (N21), step of 1,500 m - Early Miocene (N11), step of 700- 900 m - Late Pliocene- Early Pleistocene (N22 – Q11).